Silicon‐Depleted Present‐Day Earth's Outer Core Revealed by Sound Velocity Measurements of Liquid Fe‐Si Alloy. Issue 6 (13th June 2020) - Nakajima, Yoichi; Kawaguchi, Saori I.; Hirose, Kei; Tateno, Shigehiko; Kuwayama, Yasuhiro; Sinmyo, Ryosuke; Ozawa, Haruka; Tsutsui, Satoshi; Uchiyama, Hiroshi; Baron, Alfred Q. R.
Abstract: Here we determined the P wave velocity of liquid Fe84 Si16 up to 56 GPa based on inelastic X‐ray scattering measurements in a laser‐heated diamond‐anvil cell. We found that silicon significantly increases the P wave velocity of liquid iron under high pressure. The equation of state (EoS) of liquid Fe‐Si is obtained from the present sound velocity measurements. When extrapolating the present data to core pressures with the EoS, the silicon concentration must be limited to less than 1.9 − 0.5 + 1.2 wt.% in the outer core to explain its P wave velocity. In contrast, if silicon is the sole light element, 4.0 − 0.6 + 1.0 to 4.8 − 1.4 + 0.9 wt.% is necessary to account for the outer core density deficit. Thus, a liquid Fe‐Si cannot explain both the density and sound velocity simultaneously, suggesting that silicon is not the predominant light element in the core. Recent core formation models have predicted that the initial core contained 2 to 9 wt.% Si, which makes the P wave velocity much faster than that observed in the present‐day outer core. The core may have changed its composition by crystallizing SiO2 or (Mg, Fe)SiO3 . It is possible that the initial core with <4 wt.% Si and 5 wt.% O segregated from silicate under moderately oxidizing conditions and its composition evolved into a silicon‐poor one (<1.9 wt.% Si), which is compatible with the seismological observations. Such moderate Si content in the original core could also account for the high MgO/SiO2 and 30 Si/ 28 Si ratios in Earth's mantle relative to chondritic values. Key Points: Sound velocity of liquid Fe‐Si alloy was measured at high pressures to 56 GPa Silicon content in the present‐day outer core should be limited to 1.9 +1.2 −0.5 wt.% Core may have formed under moderately oxidizing conditions, and its composition may have evolved into a Si‐poor one